Math Difficulties in High School Seniors: Analysis of Results from High Schools in Costa Rica´s Indigenous Territories and the Greater Metropolitan Area - Moreira Mora, Tania Elena (2020)
The School Effectiveness Framework was used to examine three dimensions: socio-demographic characteristics, attitudes towards Math and social beliefs about Math contexts with the objective of exploring the predictive value of variables associated with difficulties in Math-related subjects for high school seniors (last year students) in Indigenous territories and the Greater Metropolitan Area of Costa Rica. The is a cross-sectional and correlational study based on a sample size of 356 students who answered four questionnaires: The Math Self-Efficacy Scale, Math Usefulness, Sexist Beliefs and Math-Gender Stereotypes. Multilevel regression models were calculated using two dependent variables: a) a count indicator for difficulties in Math-related subjects and, b) a variable identifying students who needed to take a remedial test to pass the subject. Results reveal that Math Self-Efficacy was the principal predictor of difficulties in both populations. Benevolent Sexism and Equity were also relevant only for BMA-age high school students. The explicative value of the predictors in both dependent variables is considerably higher for BMA schools. Despite contextual differences, it can be concluded that that Math Self-efficacy is a relevant predictor for indicators related to Math difficulties and its use should be promoted in classrooms. However, more research is needed, specifically in indigenous territories, to help reduce factors that are causing students to lag behind in Math in this specific population group.